Detecting sources of resistance to multiple diseases in Argentine maize (Zea mays L.) germplasm - Kistner, María Belén; Nazar, Lázaro; Montenegro, Lucía Daniela; Cervigni, Gerardo Domingo Lucio; Galdeano, Ernestina; Iglesias, Juliana (Springer Nature, 2022)
Maize (Zea mays L.), an important cereal for human and animal nutrition, is usually affected by multiple co-occurring pathogens that reduce production. Argentina is the fourth maize producer worldwide, with common rust (CR), northern corn leaf blight (NCLB), southern corn leaf blight (SCLB) and bacterial leaf streak (BLS) being important yield-limiting diseases in most maize producing areas. In this study, we aimed to identify genotypes with multiple disease resistance (MDR) for the introgression of broad-sense resistance into temperate maize breeding programs. We evaluated 87 genotypes from the Argentine public temperate inbred maize collection available from Instituto Nacional de Tecnología Agropecuaria (INTA) for their response to CR, NCLB, SCLB and BLS in up to five environments of Argentina. We compared four strategies to select sources of resistance to multiple diseases that could be used in breeding programs. Significant genotypic variation and high heritabilities were found for all disease resistances. The panel of inbred lines had numerous genotypes resistant to CR (80%) and BLS (78%), whereas genotypes resistant to NCLB (26%) or SCLB (30%) were less frequent. However, we were able to identify 12 genotypes as potential candidates for the introgression of broad-sense resistance. Our results indicate that the selection based on principal component analysis (PCA) was the most accurate methodology to detect MDR across all accessions. Maize studies based on MDR are scarce; to our knowledge, this is the first study conducted on Argentine germplasm. These findings will contribute to the strengthening of broad-sense resistance in temperate breeding programs as well as to the study of MDR detection.